(untitled) (Research, Society and Development, 2021)
Fish farming is a recent economic activity in Brazil. This paper analyzed the relations between family fishfarmers and the social actors, assessing the factors involved in the local development of Maripá/PR. It was concluded that public policies, technical assistance, associativism, industrialization and articulations provided the great growth and an intensification of the activity, making Maripá a national reference.